Ibuprofen inhibits overexpression of tumor-related Rac1b through SRSF1 - Gonçalves, Vânia (2017)
Introduction: The serrated pathway to colorectal tumor formation involves oncogenic mutations in the BRAF gene, which are sufficient for initiation of hyperplastic growth but not for tumor progression. A previous analysis of colorectal tumors revealed that overexpression of splice variant Rac1b occurs in around 80% of tumors with mutant BRAF and both events proved to cooperate in tumor cell survival. Patients with inflamed human colonic mucosa also have increased expression of Rac1b as well as mice with experimentally induced colitis. The increase of Rac1b in the mouse model was specifically prevented by the nonsteroidal anti-inflammatory drug ibuprofen.